Cr/Al Pillared Bentonite and Its Application on Congo Red and Direct Blue Removal - Muhammad Said; Afifah Rahma Dian; Risfidian Mohadi; Aldes Lesbani (Molekul, 2020)
Bentonite was modified through pillarization with metal oxide Cr/Al in 2:1 and 1:2 ratio to obtain larger basal spacing of bentonite-layered structure. Pillarization was conducted via intercalation method at room temperature followed by calcination. The result was characterized by using XRD and FT-IR Spectrophotometer. XRD pattern shown pillarization by Cr/Al 2:1 ratio gave peak at 2θ 5.3° which is correspond to d = 16.4 Å. At 1:2 Cr/Al ratio, peak appears at 2θ 6.4° that is related to d = 13.7 Å. FTIR Spectroscopy measurement gave inconclusive result. The Cr/Al pillared bentonite at 2:1 ratio was applied as adsorbent on Congo red and Direct blue dyes. The result indicates the adsorption follows Freundlich isotherm. Adsorption rate for both dyes follows pseudo-second order with rate constant of pillared bentonite higher than natural one. Adsorption isotherm concludes that Freundlich isotherm is favorable compare to Langmuir. Thermodynamic evaluation suggests that isotherm occurs spontaneously in an exothermic process.